Pengaruh Monosodium Glutamat Terhadap Pertumbuhan Vegetatif Tanaman Cabai Setan di Tanah Latosol - Faustina, Ega; Febriyono, Wahyu; Prayitno, Restu Agus (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Ghost chili have a high economic value because the level of consumption among the public is very high. Latosol soil in general is soil that has undergone further leaching so that the phosphorus (P) in the soil is acidic and bound in the form of Al-P and Fe-P compounds. Intensive fertilization on Latosol soil is needed to increase soil fertility and increase ghost chili production. MSG is an alternative fertilizer that can be used because it contains macro elements that plants need. The purpose of this reseach was to determine the effect of MSG in increasing the vegetative growth of Ghost Chili Plants in Latosol Soil. This research was conducted on the Green House of the University of Peradaban, Paguyangan District, Brebes Regency, Central Java. This research used a 3 x 3 factorial Complete Randomized Block Design. The first factor was the dose of NPK fertilizer (0 gr, 1 gr, 2 gr), while the second factor was the dose of MSG (0 gr, 2 gr, 4 gr) so that a total of 9 treatment combinations were obtained. The parameters observed were the increase in plant height, increase in the number of leaves, and increase in plant stem diameter. The results of the research showed that there was no interaction between the NPK fertilizer treatment and the MSG fertilizer treatment. Giving Monosodium Glutamate 4 grams/plant can increase plant height by 14.07 cm and the number of leaves by 9 pieces in ghost chili plants compared to the control, while giving NPK 2 grams/plant can increase plant height by 15.85 cm, number of leaves by 10 pieces and the stem diameter is 1.5 cm for ghost chili plants.